Al-Wasathiyah fî al-Iqtishâd al-Islâmî: Ârâ’u ‘ulamâ Jam’iyati “Nahdlatul Ulama” Bi Jawa al-Syarqiyah haula “al-Taraddud” bi Sya’ini Fatâwa al-Fawâid al-Mashrîfiyah - Zainal Abidin; Miftahul Ulum; Cut Linda Marheni; Umarul Faruq; Khotibul Umam (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2023)
Recently, there has been a massive innovation of online loans and good purchases using pay later with installment schemes. The phenomenon inevitably brings into controversies among the public recalling the old discussion about bank interest. Although Islamic scholars have formulated religious edict (fatwa) about bank interest, some look unfirm, such as that of NU (Nahdlatul Ulama’). This writing aims to portray the seemingly unfirm attitude of the organization relying on the assumption that it actually aims to campaign Islamic economic moderation a la NU. This is qualitative research using the phenomenological approach with the interview as the data compilation method. The opinion of 8 Kiais from the East Java NU insiders became the research subjects. The result shows how the dispute of bank interest has been becoming a continuously debatable topic. Among the three opinions about the bank interest, namely haram, halal, and shubhat, most informants choose the moderate one by neither considering it halal nor haram, including categorizing it as a part of riba type. This intersubjective opinion resonates with organizational opinion which reflects tolerance of the Indonesian monetary reality, such as Islamic banking and conventional banks which are respectively used by Indonesians. This sort of contestation takes a form of formalist and substantial moderation for bridging extreme opinions about the bank's interest.